Hacia una tipología de inundaciones en la cuenca del Ebro en función de sus causas meteorológicas - Espejo Gil, Francisco (Geographicalia, 2015)
The Ebro Basin is a greatly varied environment from both a climatic and a topographic point of view. Therefore, the flood situations affecting it show a similar degree of diversity. The systematic study of the atmospheric phase of flood situations in the basin over the last 50 years allows us to tackle a classification of these situations according to their atmospheric causes. An analysis of a selection of episodes studied homogeneously by means of modern weather numerical models for reanalysis as well as interpolation and graphical representation techniques has been made. This study, independent of the technical means at the time of each situation, has cast light on the atmospheric causes behind them. It has allowed us to establish some analogies and, therefore, to make draft classifications according to criteria such as seasonality, type and dynamism of the atmospheric situation, or the different areas affected within the basin. The relationships among these classifications have been studied as well.
Keywords: Ebro Basin; flood; atmosphere; synoptic climatology; flood typology.